2013
DOI: 10.3389/fpsyg.2013.00654
|View full text |Cite
|
Sign up to set email alerts
|

Extracting salient sublexical units from written texts: “Emophon,” a corpus-based approach to phonological iconicity

Abstract: A growing body of literature in psychology, linguistics, and the neurosciences has paid increasing attention to the understanding of the relationships between phonological representations of words and their meaning: a phenomenon also known as phonological iconicity. In this article, we investigate how a text's intended emotional meaning, particularly in literature and poetry, may be reflected at the level of sublexical phonological salience and the use of foregrounded elements. To extract such elements from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 82 publications
1
30
1
Order By: Relevance
“…Interestingly, the results of the online decision task are somewhat incongruent with recent research emphasizing the influence of foregrounded features on aesthetic appreciation (Aryani et al, 2013). For example, Aryani et al (2013) demonstrated, via use of a text analysis tool, that the salience of particular sublexical features (e.g., phonological repetition) correlates with the semantic and aesthetic properties of poetic phrases.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, the results of the online decision task are somewhat incongruent with recent research emphasizing the influence of foregrounded features on aesthetic appreciation (Aryani et al, 2013). For example, Aryani et al (2013) demonstrated, via use of a text analysis tool, that the salience of particular sublexical features (e.g., phonological repetition) correlates with the semantic and aesthetic properties of poetic phrases.…”
Section: Discussioncontrasting
confidence: 82%
“…Cynghanedd sentences thus consist of foregrounding features at the sublexical (phonological salience) and lexical (stress pattern) levels (Jacobs, 2015). Each of these features is known to independently influence aesthetic appreciation (e.g., Aryani et al, 2013; Chen et al, 2016), but their interactive effect is unclear. In the present investigation, test sentences were constructed which either adhered to the rules of Cynghanedd, or violated its rules in terms of consonantal repetition, stress pattern, or both consonantal repetition and stress pattern ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As letters and bigrams mainly correspond to phonemes, also phonological iconicity (i.e. direct correspondence between single phonemes and semantic features and the emotional tone, e.g., Aryani, Jacobs, & Conrad, 2013) might be a candidate to explain effects based on sub-lexical visual features. The early locus of the observed effects in the present study, occurring automatically at early visual-sensory processing stages suggest that contextual learning and stimulus familiarity are important factors contributing not only to emotional effects in verbal processing, but likely to emotional stimulus processing in general -revealing the necessity to control for differences in visual and sub-lexical features in future word recognition and emotion research.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we regard phonemes as units whose primary function is to create perceptual distinctions but which may sometimes also be associated with a meaning. As we already mentioned above, studies on both signed and spoken languages (de Boer, Sandler & Kirby 2012;Aryani et al 2013) suggest that the smallest units of a language are not always meaningless. The manual parameters of handshape, location, and movement, regarded as the discrete meaningless units of sign language phonology, behave like independently meaningful morphemes in classifier constructions (Sandler 2009: 261), and the distribution of certain handshapes within the lexicon has been shown to be better explained by their meaning (i.e.…”
Section: Properties Of Facial Movements Lexically Related To Signs Fomentioning
confidence: 85%
“…These categories can vary greatly between cultures, even for semantic domains that are thought to be based on universal human experiences such as color vision or feelings (Wierzbicka 1996(Wierzbicka , 1999. Words generally display duality of patterning, although this may not be a strictly universal property of words as previously assumed (de Boer, Sandler & Kirby 2012;Aryani et al 2013). Words are combinatoric; that is, they combine with each other in hierarchical patterns to form more complex semiotic structures.…”
Section: Multiple Layers Of Information In Communicationmentioning
confidence: 97%